Visual and anatomical outcomes of primary retinectomy for diabetic tractional retinal detachment - Ecem Onder Tokuc; Levent Karabas; Hatice Selen Kanar; Fatih Bilgehan Kaplan; Sevim Ayça Seyyar; Isıl Uslubas (BMC Ophthalmology)
Abstract Purpose Uncontrolled proliferative diabetic retinopathy (PDR) can cause fibrovascular growth and retinal traction, leading to tractional retinal detachment (TRD). The role of primary retinectomy in diabetic TRD remains unclear, as most studies focus on rhegmatogenous retinal detachment (RRD) with PVR. This study aims to investigate the impact of retinectomy on anatomical and visual outcomes in patients undergoing pars plana vitrectomy (PPV) for diabetic TRD. Method Patients who underwent primary retinectomy during PPV for diabetic TRD were retrospectively evaluated. Best corrected visual acuity (BCVA) before surgery and at the final follow-up, retinectomy characteristics, and final retinal attachment status were documented. TRD score, the quadrant and extent of the retinectomy, presence of macular displacement at final follow-up, and postoperative complications were evaluated. The relationship between the quadrants and extent of the retinectomy and visual acuity was also assessed. Result Thirty-eight eyes of 38 patients with mean age 60.55 ± 10.00 years were included. Mean follow-up was 23.53 ± 27.40 months. The most common locations of the retinectomy sites were extended posterior to the equator (39.5%), around the equatorial zone (34.2%), and peripheral retina (26.3%). The mean BCVA improved from 1.71 ± 0.53 logMAR to 1.48 ± 0.74 logMAR at the final follow-up. At the final visit 65.8% of patients experienced improved or maintained BCVA. Temporal retinectomy showed worse visual outcomes in the Chi-square test but not in binary logistic regression analysis. Furthermore, 26 (68.4%) eyes were attached without tamponade, 10 (26.3%) were attached under silicone oil and 2 (5.6%) remained detached under silicone oil. Conclusion These findings suggest that retinectomy, when deemed necessary in eyes with diabetic TRD, may not lead to poor functional and anatomical outcomes, contrary to some previous assumptions.